Inflation dynamics in OECD economies : the role of crude oil import price, unconventional monetary policy, and post-pandemic demand shocks - Opoku, Philemon Kwame (2024)
This paper examines the impact on inflation of crude oil import price (COIP), unconventional monetary policy (UMP), and post-pandemic demand shocks for a panel of 21 OECD countries, using panel vector autoregressive (pVAR) and local projection methods. The empirical result provides evidence that COIP shocks significantly contribute to increases in consumer price index (CPI) inflation, GDP deflator inflation and producer price index (PPI) inflation. UMP shocks, although less impactful than COIP shocks, also influence inflation. Furthermore, the most significant inflationary pressures in recent times have arisen from post-pandemic demand shocks, surpassing the effects of COIP and UMP shocks in the post-COIVD period. The findings highlight the critical role of supply-side and demand-side factors in shaping inflation dynamics in the OECD.